Desenvolvimento de um modelo de doenças inflamatórias sistêmicas em Drosophila melanogaster - Teles, Natália Melquie Monteiro (2014)
CHAPTER II: The immune system has an important role in the defense of the organisms and cytokines, such as TNF-α, are important regulators of the immune system. Eiger is the first and so far the only TNF ortholog in Drosophila melanogaster involved in the processes of insect immune response. The use of molecular tools in association with P elements are the vehicles most often used for obtaining transgenic D. melanogaster, which is a great model organism in studies of the immune system. D. melanogaster has also been used for drug testing. Steroidal anti-inflammatory drugs (SIAs) and (NSAIDs) have been administered in Drosophila melanogaster aiming to study inflammatory processes. Thus, the aim of this study was to validate an alternative, efficient, fast and economical model for the study of systemic inflammatory process controlled by anti-inflammatory drugs. We used transgenic lines of D. melanogaster to obtain individuals overexpressing Eiger in specific tissues and individuals ubiquitously expressing Eiger for further silencing testing. The existence of a visible phenotype in the individuals proved to be dependent on either the responder expression quantity or the type of tissue to which the overexpression was directed. Individuals with ubiquitous overexpression of Eiger remained in the pupal stage and showed low performance in development, which resulted in statistically significant differences compared to their parental (da-GAL4 and UAS-eiger) and wild type (Canton S). This suggests the action of a systemic inflammatory process in a ubiquitous manner that results in the death of all individuals. The action of steroidal and nonsteroidal antiinflammatory drugs did not reverse the phenotype resulting from the overexpression of Eiger. Further analyses, such as dissection followed by immunostaining, microscopy, and tests with other drugs that target inflammatory pathways, are needed to further investigate and characterize this systemic inflammatory process.